Correlations and coexistence of characteristics describing body posture and feet in children of both sexes aged 4 to 6 years - Mirosław Mrozkowiak; Karol Bibrowicz; Roland Hadlich; Piotr Kurzeja; Tomasz Szurmik (Kazimierz Wielki University, 2017)
Introduction. The process of development of physiological curvatures and the foot arch has been explored by numerous researchers in various fields of science. From the standpoint of current state of knowledge, this problem should be considered in spatial terms and with regard to the several-level biokinetic chain formed by spine, pelvis and lower limbs. The aim of this study was to determine the significance of the correlation between selected characteristics that describe the system of pelvis, spine and feet in the population of both sexes aged 4 to 6. Material and methods. The examinations conducted in a group of children and young people aged 4 to 6 years allowed for recording 2,978 observations, including 1,472 girls and 1,506 boys, and values of 121 characteristics that describe body posture and feet across individual age and sex categories. The test stand for evaluation of body posture and feet using the photogrammetric method is composed of a personal computer, software, screen and printer, and projection-reception device with a camera for measurement of selected characteristics.   Conclusions. • The most frequent and strongest correlations and their coexistence with the characteristics in the area of feet occur among girls and boys aged 5 years with characteristics of the spine-pelvis system at the age of 4 and 6 years. • No regularities and logical relationships were found between the parameters of the pelvis-spine-feet system in any age range and any sex. • Among the characteristics which describe the pelvis-spine system and are most often correlated with feet characteristics are the characteristics of the frontal plane, followed by the characteristics of the transverse plane. Furthermore, among the characteristics of the feet which are most often correlated with the parameters of the pelvis and spine system are the characteristics that describe  valgus and varus deformities of hallux and fifth toe.